A method of laser welding of an aluminum matrix composite / biphasic steel
Patent Information
- Application Number
- CN202610169794.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-06
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-02-06
AI Technical Summary
[0003]但铝基复合材料和双相钢之间的物理和化学差异,导致在常规激光焊接过程中不可控地形成脆性Al-Fe金属间化合物,该化合物多为共价键结构且热力学稳定性高,其硬度极高,但延展性和断裂韧性极低,且一旦形成便难以通过后续热处理消除
1、本发明提供一种铝基复合材料/双相钢的激光焊接方法,向铝粉和CeO2粉末的混合粉末中加入溶剂,得到Al-CeO2;将Al-CeO2负载于ZrB2p/6061Al复合材料待焊接表面,形成中间层粉末,得到预处理铝基复合材料;采用双相钢板材在上、预处理铝基复合材料在下的搭接方式,将预处理铝基复合材料和双相钢板材固定于焊接夹具中,于惰性气氛中,待中间层粉末中的溶剂挥发后,进行激光焊接。本发明的铝基复合材料/双相钢的激光焊接方法,有效改善了铝基复合材料与双相钢的焊缝冶金成分,显著提升了焊接质量,解决了现有技术存在的问题。
Smart Images

Figure CN121649576B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of laser welding technology for dissimilar materials, specifically to a laser welding method for aluminum-based composite materials / duplex steel. Background Technology
[0002] Duplex steel, composed of ferrite and martensite phases, possesses high strength, good plasticity, and corrosion resistance, and is widely used in automotive structural components, rail transportation, and other industries. Aluminum-based composites, as a widely used lightweight non-ferrous metal material, have become key lightweight materials in the automotive, high-speed rail, and aerospace fields due to their high specific strength, specific modulus, and low density. Connecting aluminum-based composites and duplex steel enables synergistic lightweighting of dissimilar materials: by combining the high strength and toughness of duplex steel with the low density and corrosion resistance of aluminum alloys, the weight of components can be significantly reduced while maintaining structural performance, improving energy efficiency. For example, the Audi A8 uses an aluminum frame, with 69% of the body made of aluminum, connected to high-strength steel components via laser welding, reducing body weight by 15%, fuel consumption by 5%–8%, and simultaneously improving handling and safety. Laser welding, as a high-energy beam joining technology, can reduce the heat-affected zone and suppress the formation of brittle phases to the greatest extent by precisely controlling the power density and pulse mode parameters, and by adding an intermediate layer and ultrasonic vibration. It is an advanced manufacturing method for welding aluminum-based composite materials / duplex steel.
[0003] However, the physical and chemical differences between aluminum matrix composites and duplex steel lead to the uncontrollable formation of brittle Al-Fe intermetallic compounds during conventional laser welding. These compounds are mostly covalently bonded and have high thermodynamic stability, extremely high hardness, but very low ductility and fracture toughness, and once formed, they are difficult to eliminate through subsequent heat treatment. Therefore, brittle Al-Fe intermetallic compounds become weak points in the welded joint. During welding cooling, the dendrites in the weld metal and the liquid film between the reinforcing phases are more prone to cracking, resulting in hot cracks. After welding, these compounds easily become the starting point for crack initiation and propagation under load, leading to a significant reduction in the tensile strength of the joint. At the same time, the thermal cycling during welding causes the crystal structure of the aluminum matrix composite to dissolve and coarsen, limiting the mechanical strength of the welded joint between the aluminum matrix composite and the duplex steel plate. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a laser welding method for aluminum-based composite materials / duplex steel. This invention utilizes duplex steel sheets and ZrB... 2pUsing 6061Al composite material as the material to be welded, and CeO2-modified Al-CeO2 as the interface control medium, by controlling the laser welding process parameters and synergistically utilizing the synergistic effect of CeO2 and nano ZrB2 particles in the laser welding process, the generation and growth of brittle Al-Fe intermetallic compounds were effectively suppressed. At the same time, weld porosity defects were eliminated, the grain structure was refined, and the interfacial bonding strength of ZrB2 / Al was improved. This solved the problem of brittle fracture and high hot cracking tendency of joints caused by excessive intermetallic compound layer in the welding of aluminum-based composite materials and duplex steel.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The purpose of this invention is to provide a laser welding method for aluminum-based composite materials / duplex steel, comprising the following steps: S1. Add solvent to the mixture of aluminum powder and CeO2 powder, and use the wetting effect of the solvent surface to regulate the rheological properties of the mixture, so that the mixture is in paste form, and obtain Al-CeO2 with good coating performance.
[0006] S2, Loading Al-CeO2 onto ZrB 2p / 6061Al composite material is used to form an intermediate layer of powder on the surface to be welded, thus obtaining a pretreated aluminum-based composite material.
[0007] S3. A duplex steel plate is placed on top, with a pretreated aluminum-based composite material underneath, and Al-CeO2 positioned in between. The pretreated aluminum-based composite material and the duplex steel plate are fixed in a welding fixture. Laser welding is performed in an inert atmosphere after the solvent in the intermediate layer powder has evaporated. During laser welding, the high-energy-density laser beam first penetrates the upper duplex steel plate, forming a deep-penetrating micropore, and then melts the lower pretreated aluminum-based composite material, forming a molten pool. Under the combined action of surface tension and gravity, the metal within the molten pool undergoes complex flow, promoting mixing between the duplex steel plate and the pretreated aluminum-based composite material, achieving element diffusion and metallurgical bonding. Simultaneously, the metal at the edge of the molten pool rapidly cools and solidifies, forming a stable weld joint profile. As the laser beam moves forward, molten pools are continuously generated, and the rear metal completely solidifies, forming a continuous and uniform weld.
[0008] Compared to laser welding without the addition of nano ZrB2 particles and CeO2 powder in the weld, the molten pool will undergo a violent Al-Fe interdiffusion reaction, forming brittle Al-Fe intermetallic compounds. The thickness and morphology of these compounds will affect the performance of the welded joint between aluminum matrix composites and duplex steel plates. Excessive thickness or continuous distribution will lead to brittle fracture of the welded joint.
[0009] During the laser welding process of this invention, nano-ZrB2 particles in the weld improve the solidification structure by refining the molten pool grains and pinning dislocations. Simultaneously, CeO2 in the intermediate layer powder adsorbs at the Al-Fe interface, inhibiting Al and Fe interdiffusion and generating a Ce-containing precipitate phase, i.e., Al... 11 Ce3 and Al 10 Fe2Ce is used to replace the formation of brittle Al-Fe intermetallic compounds such as Fe2Al5, thereby improving the toughness of the Al-Fe interface. Simultaneously, nano-ZrB2 particles and CeO2 further produce a synergistic strengthening effect: nano-ZrB2 particles can promote the precipitation behavior of Ce-containing precipitates, while Ce-containing precipitates also modify nano-ZrB2 particles to enhance their strengthening ability, i.e., by constructing a ZrB2 / Al... 10 The Fe2Ce / steel multilevel interface, and the semi-coherent ZrB2 / steel interface are modified to ZrB2 / Al. 10 Fe2Ce and Al 10 The coherent composite interface of Fe2Ce / steel enhances the mechanical properties of the weld by reducing interfacial stress concentration of nano-ZrB2 particles and increasing bonding strength by lowering lattice mismatch and atomic interface roughness.
[0010] Preferred, ZrB 2p The 6061Al composite material was synthesized in situ by melt reaction method.
[0011] Preferred, ZrB 2p In the / 6061Al composite material, the mass fraction of nano-ZrB2 particles is 4wt%~8wt%; among them, when the mass fraction of nano-ZrB2 particles is less than 4wt%, the nano-ZrB2 particles have a greater influence on ZrB2 content. 2p The insufficient reinforcement of the 6061Al composite material limits its performance improvement; when the mass fraction of nano ZrB2 particles is higher than 8wt%, it is prone to particle agglomeration and interface defects.
[0012] Preferably, in the mixture of aluminum powder and CeO2 powder, the mass fraction of CeO2 powder is 30wt%~60wt%. When the mass fraction of CeO2 is less than 30wt%, its inhibitory effect on brittle Al-Fe intermetallic compounds is insufficient, resulting in a significant increase in joint brittleness. When the mass fraction of CeO2 is greater than 60wt%, the proportion of aluminum powder is too low, which will seriously weaken the fluidity of the molten pool and increase the risk of incomplete fusion.
[0013] Preferably, the diameter of CeO2 powder is 60nm~100nm, and the diameter of aluminum powder is 70μm~150μm. If the CeO2 particle size is too large, i.e. >100nm, its inhibitory effect on brittle Al-Fe intermetallic compounds is weakened; if the aluminum powder is too fine, i.e. <70μm, it is easy to oxidize and burn off and destroy the stability of the molten pool.
[0014] Preferably, on the surface of the pretreated aluminum-based composite material to be welded, the loading of the intermediate layer powder is 22 mg / cm³. 2 ~40mg / cm 2 Loading capacity less than 22 mg / cm³ 2 At this time, it can easily lead to uneven coverage and uncontrolled local brittle Al-Fe intermetallic compounds; above 40 mg / cm³ 2 Excessive light absorption or reduced thermal efficiency can lead to incomplete melting and residue of the intermediate layer powder.
[0015] Preferably, the laser power for laser welding is 1500W~2000W, and the welding rate is 15mm / s~24mm / s. Insufficient power or excessive welding rate will result in welding defects with insufficient penetration. Excessive laser power or excessive welding rate will result in excessive heat input, leading to excessive thickening of brittle Al-Fe intermetallic compounds, i.e., >15μm, which will cause a sharp increase in the tendency for hot cracking.
[0016] Preferably, the pretreated aluminum-based composite material and the duplex steel plate have the same length, width and height.
[0017] Preferably, the overlap length between the duplex steel sheet and the pretreated aluminum matrix composite material in the width direction is >8mm.
[0018] Preferably, laser welding is performed using the keyhole welding mode of the IPGYLS-4000 equipment, wherein the welding parameters are set as follows: laser wavelength of 1060nm~1065nm, focal length of 400mm, and defocusing amount of 0mm.
[0019] Preferably, the inert atmosphere is argon, with a purity of 99.999% and a flow rate of 15 L / min to 20 L / min.
[0020] Preferably, before laser welding, ZrB is also treated with 400-grit sandpaper. 2p The surfaces of the 6061Al composite material and duplex steel sheet to be welded are finely ground, cleaned, and dried to remove ZrB. 2p Oxides and oil stains on the surfaces of 6061Al composite materials and duplex steel sheets to be welded.
[0021] Preferably, ZrB is also subjected to loading before Al-CeO2. 2p The surface of the 6061Al composite material to be welded is grooved.
[0022] Preferably, the solvent is acetone or anhydrous ethanol.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a laser welding method for aluminum-based composite materials / duplex steel, wherein a solvent is added to a mixture of aluminum powder and CeO2 powder to obtain Al-CeO2; the Al-CeO2 is then loaded onto ZrB 2p A pretreated aluminum-based composite material is formed on the surface of the 6061Al composite material to be welded, creating an intermediate layer of powder. The pretreated aluminum-based composite material and the dual-phase steel plate are then joined in an overlapping manner, with the dual-phase steel plate on top and the pretreated aluminum-based composite material underneath. The two materials are fixed in a welding fixture, and laser welding is performed in an inert atmosphere after the solvent in the intermediate layer powder has evaporated. This laser welding method for aluminum-based composite materials / dual-phase steel effectively improves the metallurgical composition of the weld between the aluminum-based composite material and the dual-phase steel, significantly enhances the welding quality, and solves the problems existing in the prior art.
[0024] In suppressing brittle Al-Fe intermetallic compounds in welds, the introduction of CeO2 can effectively inhibit the formation of brittle Al-Fe intermetallic compounds, reduce the defect density and crack tendency in the weld fusion line region, and its mechanism of action mainly includes: First, CeO2 hinders the interdiffusion reaction of Al and Fe through solute dragging, significantly reducing the formation of brittle Al-Fe intermetallic compounds and alleviating stress concentration caused by interfacial brittle compounds; Second, Ce reacts in situ with Al and Fe elements in the weld to form a ductile transition layer containing Ce precipitates, the main component of which is Al. 11 Ce3 and Al 10 Fe2Ce has the ability to bridge dislocations and cracks.
[0025] 2. Regarding the reduction of acicular phases in welds, nano-ZrB2 particles and Al 10 Fe2Ce and Al 11 Ce3 inhibits the growth of brittle Al-Fe intermetallic compounds by disrupting the Al / Fe atomic diffusion pathway, reducing the number and size of acicular phases, and decreasing the likelihood of microcrack initiation and propagation at the interface.
[0026] 3. In terms of improving weld formation, CeO2 and nano-ZrB2 particles synergistically enhance weld penetration and width, reduce forming defects, and improve the joint strength of aluminum-based composites and duplex steels. This is attributed to the introduction of CeO2 and nano-ZrB2 particles, which significantly enhance the absorption capacity of aluminum and steel in the weld for laser energy, prolonging the molten pool existence time to broaden the time window for gas escape. Simultaneously, CeO2 increases the fluidity of the molten pool, promoting faster gas escape and effectively eliminating porosity defects in the weld after solidification of the molten metal. Furthermore, the laser absorption enhancement effect of CeO2 lowers the welding heat input threshold, enabling welding at lower power densities to control the heat-affected zone, reduce welding deformation and residual stress, and improve the precision and quality of welded products.
[0027] 4. Regarding weld microstructure optimization, the simultaneous introduction of CeO2 and nano-ZrB2 particles produces a synergistic strengthening effect. Compared to introducing CeO2 or nano-ZrB2 particles alone, the microstructure optimization effect of this invention is more significant: on the one hand, the heterogeneous nucleation effect of nano-ZrB2 particles promotes Al... 10 Fe2Ce and Al 11 Precipitation behavior of Ce3 phase. CeO2 in the molten pool has high surface activity; therefore, Ce readily reacts with elements in the weld, such as Fe and Al, to form finely dispersed Al phases. 11 Ce3 and Al 10 The formation of Fe2Ce precipitate can prevent or reduce the formation of brittle Al-Fe intermetallic compounds. Simultaneously, the precipitate, together with nano-ZrB2 particles, can provide more heterogeneous nucleation sites for weld metal dendrites, promoting grain refinement; Al 11 Ce3 can adsorb and purify impurity elements such as Zr in the grains, and optimize their geometry through Zr: Zr can inhibit Al... 11 The excessive growth of Ce3, while simultaneously increasing Al 11 The Ce3 phase changes from a sharp-edged, coarse blocky shape to a rounded, irregular shape, which can reduce the stress and strain concentration at the corners of the precipitated phase and enhance its strengthening effect on weld performance.
[0028] On the other hand, Ce-containing precipitates such as Al 10 Fe2Ce and Al 11 Ce3 can adhere to or coat the surface of nano-ZrB2 particles. As nano-ZrB2 particles and ZrB... 2p The transition layer between the aluminum matrix and the ZrB2 nanoparticles in the / 6061Al composite material improves the interaction between the ZrB2 nanoparticles and ZrB2. 2p The wettability of the aluminum matrix interface in the / 6061Al composite material promotes the uniform distribution of nano-ZrB2 particles, improves interfacial bonding, and enhances the composite strengthening effect of nano-ZrB2 particles. Simultaneously, Ce-containing precipitates adhere to the sharp edges of the nano-ZrB2 particles, improving their geometry and alleviating stress concentration at the corners. However, simply adding nano-ZrB2 particles increases stress concentration zones in the weld, making it more prone to cracking.
[0029] 5. In terms of improving mechanical properties, nano-ZrB2 particles increase the synthesis of Ce-containing precipitates. Ce-containing precipitates can inhibit the formation of brittle Al-Fe intermetallic compounds and acicular phases. Ce-containing precipitates can also modify the ZrB2 interface to improve its interfacial wettability and bonding strength, thereby optimizing the micro-dispersion and strengthening effect of nano-ZrB2 particles. At the same time, both CeO2 and nano-ZrB2 particles can refine the matrix grains, inhibit the generation and propagation of weld cracks, and improve weld formation, thereby optimizing the weld microstructure and improving the mechanical properties of the joint. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of a laser welding method for aluminum-based composite materials / duplex steel.
[0031] Figure 2 A schematic diagram of an apparatus for loading duplex steel sheets and aluminum-based composite sheets onto a welding fixture.
[0032] Figure 3 The images show cross-sectional views of the welds in Example 1 and Comparative Examples 1 to 3; where (a) is Comparative Example 1, (a1) is an enlarged view of the box a1 in (a), (b) is Comparative Example 2, (b1) is an enlarged view of the box b1 in (b), (c) is Comparative Example 3, (c1) is an enlarged view of the box c1 in (c), and (d) is Example 1, (d1) is an enlarged view of the box d1 in (d).
[0033] Figure 4 The images show IPF diagrams of weld sections for Example 1 and Comparative Examples 1 to 3; where (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Example 1.
[0034] Figure 5 The KAM diagrams of the weld cross sections of Example 1 and Comparative Examples 1 to 3 are shown; where (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, and (d) is Example 1.
[0035] Figure 6 The images show the tensile fracture morphology of the weld seams in Example 1 and Comparative Examples 1 to 3. In Comparative Example 1, (a1) is an enlarged view of the box in (a1), (a2) is an enlarged view of the box in (a2), (b) is Comparative Example 2, (b1) is an enlarged view of the box in (b1), (b2) is an enlarged view of the box in (b2), (c) is Comparative Example 3, (c1) is an enlarged view of the box in (c1), (c2) is an enlarged view of the box in (c2), and (d) is Example 1, (d1) is an enlarged view of the box in (d1), and (d2) is an enlarged view of the box in (d2).
[0036] Figure 7The diagrams show the distribution of nanophases in the weld seams of Example 1 and Comparative Example 1. In Comparative Example 1, (a1) shows the distribution of Fe in (a), (a2) shows the distribution of Al in (a), (a3) shows the distribution of Ce in (a), and (a4) shows the distribution of Si in (a). In Example 1, (b1) shows the distribution of Fe in (b), (b2) shows the distribution of Al in (b), (b3) shows the distribution of Ce in (b), and (b4) shows the distribution of Zr in (b).
[0037] Figure 8 For example, ZrB2 and Al in the weld of Example 1 10 Fe2Ce, Al 11 Electron microscopy results of Ce3; where (a) shows ZrB2 and Al. 10 Fe2Ce, Al 11 The HRTEM image of Ce3, the inset in (a) is the area enclosed by the yellow dashed line in (a), which is Al. 10 The IFFT plots of Fe2Ce, (a1) is the HRTEM plot at the interface between ZrB2 and the aluminum matrix, and (a2) is the plot at the interface between ZrB2 and Al. 10 HRTEM image at the Fe2Ce interface, (a3) shows Al 11 The HRTEM plot of Ce3, (a4) is the SAED plot within box a4 in (a), (a5) is the distribution plot of Fe element in (a), (a6) is the distribution plot of Al element in (a), (a7) is the distribution plot of Ce element in (a), and (a8) is the distribution plot of Zr element in (a).
[0038] Figure 9 For example, ZrB2 and Al in the weld of Example 1 11 Electron microscopy results of Ce3; where (a) shows ZrB2 and Al. 11 The HRTEM image of Ce3, (a1) is an enlarged view of the area selected in red in (a), and (a2) is an Al 11 HRTEM image of Ce3, (a3) is Al 11 HRTEM images of the Ce3-aluminum matrix interface, (a4) showing the distribution of Fe in (a), (a5) showing the distribution of Al in (a), (a6) showing the distribution of Ce in (a), (a7) showing the distribution of Zr in (a), and (a8) showing the distribution of Al... 11 The IFFT plot of Ce3, (b1) is an enlarged view of the area selected in blue in (a1), (b2) is the HRTEM plot of ZrB2, and (b3) is the HRTEM plot of the interface between ZrB2 and the aluminum matrix.
[0039] Figure 10The figures show the microhardness distribution of the welded joints in Example 1 and Comparative Examples 1 to 3, where the inset shows the location of the measurement points selected when measuring the hardness of the weld using a hardness tester.
[0040] Figure 11 The diagrams show the force-displacement and tensile strength of the welded joints in Example 1 and Comparative Examples 1 to 3; (a) is the force-displacement diagram of the welded joint; and (b) is the tensile strength diagram of the welded joint.
[0041] Reference numerals: 1. Laser beam for welding; 2. Intermediate layer powder; 3. Duplex steel sheet; 4. Aluminum-based sheet; 5. Substrate. Detailed Implementation
[0042] The technical solution of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0043] It should be noted that the technical terms used in this invention are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased commercially or prepared by existing methods. The purity of KBF4 and K2ZrF6 is 98%.
[0044] In existing technologies, the physical and chemical differences between aluminum matrix composites and duplex steel sheets lead to the uncontrollable formation of brittle Al-Fe intermetallic compounds during welding. This makes the metal dendrites and the liquid film between the reinforcing phases more prone to cracking during welding cooling. These compounds easily become the starting point for crack initiation and propagation under load after welding, severely affecting the welding quality of aluminum matrix composites and duplex steel sheets. The thermal cycling during welding causes the crystal structure of the aluminum matrix composite to dissolve and coarsen, significantly reducing the mechanical strength of the welded joint between the aluminum matrix composite and duplex steel sheets.
[0045] To address the brittle fracture problem caused by intermetallic compounds, a CeO2-modified Al-CeO2 interlayer was introduced. The adsorption effect of CeO2 at the Al / Fe interface suppressed the interdiffusion of Al and Fe elements, significantly reducing the formation and thickness of brittle Al-Fe intermetallic compounds, such as Fe2Al5. Simultaneously, ZrB2 nanoparticles were synergistically used to construct a ZrB2 / Al... 10 The Fe2Ce / steel multi-level coherent interface reduces lattice mismatch and fundamentally improves interface toughness.
[0046] To address the coarsening of precipitate phases caused by thermal cycling, in-situ synthesized nano-ZrB2 particles were used to pin dislocations and refine the melt pool grains, thus suppressing coarsening of the precipitate phases in the heat-affected zone. Simultaneously, Ce-containing precipitate phases (Al...) were also employed. 11 Ce3, Al 10 Fe2Ce) purifies grain boundary impurities, further stabilizing the microstructure and ensuring joint strength and toughness.
[0047] To address the problem of porosity defects in the molten pool, CeO2 is used to enhance laser energy absorption efficiency, prolong the molten pool's existence time, reduce the viscosity of the molten metal, and widen the gas escape window. Combined with precisely controlled laser parameters, the molten pool flow is optimized, completely eliminating porosity defects.
[0048] In this invention, ZrB 2p The 6061Al composite material is a 6061 aluminum-based composite material reinforced with nano-ZrB2 particles, synthesized in situ using a melt reaction method.
[0049] Method 1: Weigh 6061Al, KBF4, and K2ZrF6 according to a mass ratio of 125:4:4.5. Mix KBF4 and K2ZrF6 and dry them at 150℃ for 1 hour to obtain a mixed salt. Simultaneously, place 6061Al in a crucible, melt it in an induction furnace, and heat it to 810℃ to obtain 6061Al melt. Add the mixed salt to the 6061Al melt and react in situ for 30 minutes to generate nano-ZrB2 particles. After the reaction is complete, cool the mixture to 700℃, pour the melt into a preheated mold at 140℃, and then perform a solution treatment at 470℃ for 2 hours, followed by a T6 heat treatment at 120℃ for 24 hours to obtain 4wt% ZrB2. 2p / 6061Al composite material, i.e. ZrB 2p / 6061Al composite material.
[0050] Method 2: Same as Method 1, except that the mass ratio of 6061Al, KBF4 and K2ZrF6 is replaced from 125:4:4.5 to 125:8:9, resulting in 8wt% ZrB. 2p / 6061Al composite material, i.e. ZrB 2p / 6061Al composite material.
[0051] To enable those skilled in the art to more clearly understand the technical solution of the present invention, a detailed description will be provided below in conjunction with specific embodiments. Specifically, ZrB in Embodiment 1 and Comparative Example 3... 2p The 6061Al composite materials were all prepared by method one.
[0052] Example 1 A laser welding method for aluminum-based composite materials / duplex steel includes the following steps: S1. Use 400-grit sandpaper to polish ZrB. 2p The / 6061Al composite material and duplex steel plate are finely ground at the welding parts, then cleaned with an ultrasonic cleaner, and then dried to remove oxides and oil stains from the surface of the welding parts, resulting in aluminum-based plate 4 and duplex steel plate 3; wherein the dimensions of aluminum-based plate 4 and duplex steel plate 3 are: length 100mm, width 50mm, and thickness 1mm.
[0053] S2. Aluminum powder with a diameter of 70 μm and CeO2 powder with a diameter of 100 nm are uniformly mixed to obtain a mixed powder; wherein, the mass fraction of CeO2 powder in the mixed powder is 40 wt%; the mixed powder is ball-milled at 200 rpm for 2 hours to ensure uniform distribution of aluminum powder and CeO2 powder; then acetone is added to the mixed powder to make the mixed powder into a paste to obtain Al-CeO2.
[0054] S3. Al-CeO2 is pre-coated onto the surface of the aluminum substrate 4 to be welded. The Al-CeO2 coated on the surface of the aluminum substrate 4 to be welded is designated as intermediate layer powder 2. The coating amount of intermediate layer powder 2 is 35 mg / cm³. 2 .
[0055] S4. Load the aluminum-based plate 4 and duplex steel plate 3 onto the general welding fixture, and set the substrate 5. Adopt the duplex steel plate 3 on top and the aluminum-based plate 4 on the bottom, with an overlap length of 10mm in the width direction. Offset the laser head 10° in the welding direction. Install the protective gas device and use argon gas for welding protection. The argon gas purity is 99.999% and the argon gas flow rate is 20L / min. After the acetone in the intermediate layer powder 2 has completely evaporated, laser welding is performed using the laser keyhole welding mode of the IPGYLS-4000 laser welding equipment. The welding parameters are set as follows: laser wavelength is 1064nm, focal length is 400mm, defocusing amount is 0mm, laser power is 1900W, and welding speed is 22mm / s.
[0056] Overall overlapping method as follows Figure 1 and Figure 2 As shown, the weld cross-section after welding is as follows: Figure 3 As shown in (d), (d1), and (d2), the IPF diagram is as follows: Figure 4 As shown in (d) in the figure, the fracture surface microstructure is as follows: Figure 6 As shown in (d) above, the distribution of nanoparticles within the weld is as follows: Figure 7 As shown, nano ZrB2 particles, Al 10 TEM image of Fe2Ce as shown Figure 8 As shown, Al 11 TEM image of Ce3 as follows Figure 9As shown.
[0057] Example 2 A laser welding method for aluminum-based composite materials / duplex steel is the same as that in Example 1, except that the diameter of the aluminum powder in S2 is replaced from 70 μm to 150 μm, the diameter of the CeO2 powder is replaced from 100 nm to 60 nm, the mass fraction of CeO2 powder in the mixed powder is replaced from 40 wt% to 30 wt%, and the loading of the intermediate layer powder in S3 is changed from 35 mg / cm³. 2 Replace with 22mg / cm 2 The laser power in S4 was changed from 1900W to 2000W, and the welding speed was changed from 22mm / s to 24mm / s.
[0058] Example 3 A laser welding method for aluminum-based composite materials / duplex steel is the same as that in Example 1, except that the mass fraction of CeO2 powder in the mixed powder is replaced from 40wt% to 60wt%, and the loading of S3 interlayer powder is changed from 35mg / cm³. 2 Replace with 40mg / cm 2 The laser power in S4 was changed from 1900W to 1500W, and the welding speed was changed from 22mm / s to 15mm / s.
[0059] Comparative Example 1 A laser welding method for aluminum alloy / duplex steel is the same as that in Example 1, except that ZrB in S1 is used instead of ZrB. 2p The 6061Al composite material is replaced with 6061 aluminum alloy. Operations S2 and S3 are omitted; only S1 and S4 are performed. In S4, it is not necessary to wait for the solvent acetone to completely evaporate. The overall overlap method is as follows: Figure 1 , Figure 2 As shown. The weld cross-section after welding is as follows. Figure 3 As shown in (a) and (a1) in the figure, the IPF diagram is as follows: Figure 4 As shown in (a) above, the KAM diagram is as follows: Figure 5 As shown in (a) above, the fracture surface microstructure is as follows: Figure 6 As shown in (a) of the diagram.
[0060] Comparative Example 2 A laser welding method for aluminum alloy / duplex steel is the same as that in Example 1, except that ZrB in S1 is used instead. 2p The 6061Al composite material was replaced with 6061 aluminum alloy, and operations S1, S2, S3, and S4 were performed sequentially. The overall overlapping method is as follows: Figure 1 , Figure 2 As shown, the weld cross-section after welding is as follows: Figure 3As shown in (b) and (b1) in the figure, the IPF diagram is as follows: Figure 4 As shown in (b) of the diagram, the KAM diagram is as follows: Figure 5 As shown in (b) above, the fracture surface microstructure is as follows: Figure 6 As shown in (b) of the diagram.
[0061] Comparative Example 3 A laser welding method for aluminum-based composite materials / duplex steel is the same as that in Example 1, except that operations S2 and S3 are omitted, and only operations S1 and S4 are performed. Furthermore, in S4, it is not necessary to wait for the solvent acetone to completely evaporate. The overall overlapping method is as follows: Figure 1 , Figure 2 As shown. The weld cross-section after welding is as follows. Figure 3 As shown in (c) and (c1) in the figure, the IPF diagram is as follows: Figure 4 As shown in (c) in the figure, the KAM diagram is as follows: Figure 5 As shown in (c), the fracture surface microstructure is as follows: Figure 6 As shown in (c) in the figure.
[0062] Table 1 shows the laser welding process parameters for Example 1 and Comparative Examples 1 to 3.
[0063] After welding, cross-sections of the samples from Example 1 and Comparative Examples 1 to 3 were cut using a wire EDM machine. The standard metallographic samples were then mounted, ground, and polished. The microstructure was characterized using optical microscopy, scanning electron microscopy, electron backscatter diffraction, and transmission electron microscopy. The average hardness of the welded area was measured using a Vickers hardness tester with a force of 200g. The hardness distribution of the four welded joints is shown below. Figure 10 As shown. The tensile results of the four sets of welded joints are as follows. Figure 11 As shown.
[0064] Because aluminum has a lower density than steel, some aluminum floats to the surface in the molten pool and mixes with the steel, undergoing an interfacial reaction to form brittle Al-Fe intermetallic compounds, which severely affects the joint strength. (Observation) Figure 3 From (a1) and (c1), it is concluded that cracks exist at the interface of the welded joints in Comparative Example 1 and Comparative Example 3. Observation Figure 3 As shown in (b1) and (d1), the number of cracks at the weld joint interface is reduced after the addition of Ce. This is because Ce improves the microstructure of the weld metal, significantly enhancing its thermal stability and resistance to deformation. Simultaneously, some Ce phases can encapsulate nano-ZrB2 particles, reducing the exposure of their sharp edges in the matrix, alleviating stress concentration, and thus inhibiting crack initiation. Therefore, using Ce as an intermediate layer in aluminum / duplex steel welding can reduce the occurrence of welding hot cracks, thereby improving the strength of the weld joint.
[0065] Furthermore, the introduction of CeO2 helps reduce the thickness of the intermetallic compound layer in the weld joint and refines the size of the acicular phase. Figure 3 From (a1) and (b1), it is found that after adding CeO2, the typical thickness of the brittle Al-Fe intermetallic compound layer at the aluminum / duplex steel interface decreased from 5.21 μm to 4.64 μm. Figure 3 From (c1) and (d1), the typical thickness of the brittle Al-Fe intermetallic compound layer at the aluminum matrix composite / duplex steel interface decreased from 2.1 μm to 1.69 μm. Simultaneously, compared to welded joints without CeO2, the typical length of the acicular phase in Ce-containing joints was significantly reduced: the size at the aluminum / duplex steel interface decreased from 8.86 μm to 4.79 μm, and the size at the aluminum matrix composite / duplex steel interface decreased from 5.72 μm to 4.62 μm. These results indicate that the addition of Ce can effectively improve the microstructure of the intermetallic compound, thereby reducing the tendency of the joint to brittle fracture.
[0066] Nano-sized ZrB2 particles also help reduce weld cracking and inhibit the formation of brittle Al-Fe intermetallic compounds. Figure 3 As shown in (a1), (b1), (c1), and (d1), obvious cracks were observed in the welded joints of Comparative Example 1 and Comparative Example 2 without the addition of nano-ZrB2 particles, with brittle Al-Fe intermetallic compound layer thicknesses of 5.21 μm and 4.64 μm, respectively. However, in the welded joints of Comparative Example 3 and Example 1 with the introduction of nano-ZrB2 particles, the number and size of cracks were significantly reduced, and the brittle Al-Fe intermetallic compound layer thicknesses were 2.1 μm and 1.69 μm, respectively. This is because the grain refinement and strengthening effect of nano-ZrB2 particles on the aluminum alloy partially offsets stress concentration, thus reducing the cracking tendency. Furthermore, the dispersed nano-ZrB2 particles can anchor at interfaces or grain boundaries, effectively hindering the interdiffusion of Fe and Al elements, limiting the excessive growth of the brittle Al-Fe intermetallic compound layer, and ultimately forming a thinner intermetallic compound layer.
[0067] In summary, the simultaneous introduction of CeO2 and nano-ZrB2 particles into the weld exhibits a synergistic strengthening effect due to the encapsulation behavior of CeO2 on the nano-ZrB2 particles, resulting in optimal crack suppression during welding and effectively reducing the formation of brittle Al-Fe intermetallic compound layers and acicular phases. Furthermore, compared to adding CeO2 alone or introducing only nano-ZrB2 particles, the simultaneous addition of CeO2 and nano-ZrB2 particles significantly improves grain refinement. Figure 4 As shown.
[0068] according to Figure 5The results show that, compared with adding CeO2 alone or introducing only nano ZrB2 particles, adding both CeO2 and nano ZrB2 particles can significantly reduce stress and strain in the weld.
[0069] Figure 6 The SEM morphology of the tensile fracture surface of the welded joint is shown. All fractures occurred in the softest weld fusion zone caused by the dissolution of precipitates. Comparative Example 1 shows a few cracks and large cleavage planes on the fracture surface, see [image / description]. Figure 6 The values (a), (a1), and (a2) indicate that the fracture mode is mainly intergranular fracture. The fracture surface of Comparative Example 2 is characterized by small, deep dimples, with some areas exhibiting a riverbed-like morphology. Figure 6 (b), (b1), and (b2) are shown in Figure 3. In contrast, the fracture surface of Comparative Example 3 shows that some brittle fracture areas exhibit a small, candy-like morphology, as seen in Figure 3. Figure 6 (c), (c1), and (c2) in the text.
[0070] The fractures in Comparative Examples 1 and 3 were due to the presence of numerous brittle Al-Fe intermetallic compounds at the grain boundaries, which readily became the source of crack initiation and propagation. As the cracks propagated along the grain boundaries, the weak intergranular bonding caused them to detach from the matrix, resulting in a candy-like morphology.
[0071] like Figure 6 As shown in (d) and (d1), a large number of dimples were observed in the fracture surface of Example 1, and nano ZrB2 particles and Al were detected in the dimples. 11 Ce3 and Al 10 Fe2Ce phase. The presence of tearing ridges around the nano-ZrB2 particles indicates a strong interfacial bond between the nano-ZrB2 particles and the weld matrix. During tensile deformation, dislocation movement is influenced by the nano-ZrB2 particles and Al... 11 Ce3 and Al 10 The obstruction of the Fe2Ce phase leads to the accumulation of dislocations around it, inducing micropore nucleation under high stress and strain. The aggregation of numerous micropores ultimately causes the welded joint to fracture, forming a structure resembling... Figure 6 The pitted fracture morphology shown in (d2) indicates that the main fracture mode of Example 1 is ductile transcrystalline fracture. Furthermore, the proportion of fine dimples in its fracture surface is higher than that of Comparative Examples 1 to 3, indicating that the former has superior ductility. This fracture surface feature is similar to... Figure 11 The stretching results are consistent.
[0072] like Figure 7As shown, both Comparative Example 1 and Example 1 contain a small amount of nanophase concentrated at the grain boundaries and interdendritic interfaces. The nanophase in Comparative Example 1 is mainly composed of brittle Al-Fe intermetallic compounds with an average size between 40 nm and 50 nm. These brittle Al-Fe intermetallic compounds exhibit lattice mismatch with the aluminum and dual-phase steel matrix, and their high interfacial energy at the interface easily induces crack initiation and promotes crack propagation. In the weld of Example 1, a large number of Al phases with a size of 20 nm to 30 nm are uniformly distributed. 11 Ce3 and Al 10 Fe2Ce phase. These precipitates often form coherent or semi-coherent interfaces with the matrix, which helps to enhance dislocation strengthening and load transfer strengthening mechanisms, thereby improving the overall performance of the weld.
[0073] In summary, Example 1 demonstrates a synergistic strengthening effect between nano-ZrB2 particles and CeO2 during the welding process, which constitutes the main technical advantage of this invention. The following is a more in-depth physicochemical analysis in three aspects.
[0074] First: Nano-ZrB2 particles can enhance the precipitation behavior of Ce-containing precipitates during the solidification of the molten pool, i.e., Al 10 Fe2Ce and Al 11 Ce3, along with Ce-containing precipitates, can modify nano-ZrB2 particles to enhance their reinforcing ability.
[0075] Figure 8 This is a TEM image of nano-ZrB2 particles in the weld of Example 1. Figure 8 As shown in (a4), (a5), (a6), (a7), and (a8), based on elemental surface scanning and lattice spacing analysis, the regular hexagonal particle is determined to be a single hexagonal nano-ZrB2 particle. The precipitated phases attached to the surface of the nano-ZrB2 particle and near its interface with the aluminum matrix are Al, respectively. 10 Fe2Ce and Al 11 Ce3. Literature indicates that the main intermetallic compounds formed during aluminum / steel welding are Fe2Al5 and FeAl3, and these brittle compounds are one of the key factors leading to the deterioration of the joint's mechanical properties. Due to the high chemical reactivity of the rare earth element Ce, it preferentially reacts with Al and Fe elements in the weld to form Al3+. 11 Ce3 and Al 10 The Fe2Ce precipitate phase inhibits the formation of brittle compounds Fe2Al5 and FeAl3.
[0076] The reasons why nano ZrB2 particles promote the formation of Ce-containing precipitates are as follows: Figure 8As shown in (a1), the IFFT image at the ZrB2 / aluminum matrix interface reveals significant lattice distortion in the interface region. Calculations show a lattice mismatch ratio of 8.1%, indicating a semi-coherent interface. This high interface density allows for the generation of numerous mismatched dislocations near the nano-ZrB2 particles. These dislocations provide rapid diffusion channels for solute atoms, thereby promoting the precipitation of nano-Ce-containing precipitates on the particle surface. Furthermore, compared to the brittle Al-Fe intermetallic compound and the original Mg2Si precipitate present in Comparative Example 1, the Ce-containing precipitate generated in Example 1, such as Al... 10 Fe₂Ce exhibits higher thermal stability and is less prone to dissolution or coarsening during welding, which helps promote the rapid precipitation of more fine Ce-containing phases. This phenomenon is mainly attributed to the extremely low solubility of Ce in the Al / Fe matrix and its small diffusion coefficient.
[0077] Meanwhile, Ce-containing precipitates can modify nano-ZrB2 particles: such as Figure 8 As shown in (a2) and (a3), ZrB2 / Al 10 Fe2Ce and Al 10 The calculated lattice mismatch ratios between Fe2Ce and the aluminum matrix were 3.1% and 2.4%, respectively, with no significant lattice distortion observed. This was achieved by constructing a ZrB2 / Al matrix. 10 Fe2Ce / aluminum matrix precipitation-assisted interface, the originally semi-coherent ZrB2 / aluminum matrix interface was modified into ZrB2 / Al 10 Fe2Ce and Al 10 The eutectic multiple interface is composed of Fe2Ce / aluminum matrix. This structural modification effectively reduces the degree of lattice mismatch in the matrix and reduces the interfacial roughness at the atomic scale, which can improve the interfacial bonding and load transfer performance of ZrB2 / Al, promote the uniform dispersion of nano ZrB2 particles in the weld, and enhance the composite strengthening effect of nano ZrB2 particles.
[0078] Second, as a surface-active atom, Al 11 Ce3 can purify impurity elements such as Zr in the grains and further enhance Al through its modification effect. 11 The strengthening effect of Ce3 on welds. From Figure 9 Al is shown in (a), (a1), (a2), (a3), and (a8). 11 The Ce3 lattice fringes show that its lattice distortion is extremely small, with a mismatch ratio of 6% with the matrix, indicating that it belongs to a semi-coherent interface. The interface possesses interfacial energy that allows it to adsorb other elements.
[0079] according to Figure 9 The surface scan results of (a4), (a5), (a6), and (a7) in the image, and the relationship between Zr elements and Al. 11The distribution trend of Ce3 was basically consistent, indicating that Zr tends to adsorb onto Al. 11 On specific crystal planes of the Ce3 phase, the migration of Ce atoms is suppressed, thus hindering the further growth of this phase. With the addition of Zr, primary Al... 11 The Ce3 phase transforms from a coarse, massive, and sharply angular morphology to something like... Figure 9 The rounded and irregular shape shown in (a1) effectively reduces stress and strain concentration at the corners of the precipitated phase. As the main reinforcing phase, Al... 11 Ce3 can promote the formation of geometrically necessary boundaries during weld solidification, thereby achieving grain refinement and enhancing its strengthening effect on weld performance.
[0080] Third, the rare earth element Ce can reduce the micro-stress concentration of nano-ZrB2 particles and promote their uniform distribution in the weld. This can be further confirmed by lattice spacing analysis and surface scanning results. Figure 9 In (a1), the nanoparticles within the blue box are ZrB2. The original ZrB2 nanoparticles are hexagonal with sharp edges, making them prone to crack initiation and propagation; however, after modification with Ce, their sharp edges become more rounded, as... Figure 9 As shown in (b1), (b2) and (b3).
[0081] Depend on Figure 10 The results showed that the heat-affected zone (HAZ) sizes of Comparative Examples 1, 2, 3, and 1 successively narrowed, while the average weld hardness successively increased. This is because the thermal conductivity of nano-ZrB2 particles is only one-quarter that of Al. Therefore, the heat input diffusing to the surrounding aluminum matrix is reduced, resulting in a narrower HAZ.
[0082] Depend on Figure 11 The maximum tensile strengths of the welded joints obtained by the laser welding processes in Comparative Examples 1, 2, 3, and 1 were 1734 N, 2054 N, 2970 N, and 3485 N, respectively. As described above, Example 1 employed a method of simultaneously adding a high mass fraction of CeO2 and introducing nano-ZrB2 particles into the weld, resulting in synergistic strengthening by CeO2 and nano-ZrB2 particles: the nano-ZrB2 particles promote the synthesis of Ce-containing precipitates, which inhibit the formation of brittle Al-Fe intermetallic compounds and acicular phases; on the other hand, Ce and Ce-containing precipitates can modify the interface of the nano-ZrB2 particles, improving their interfacial wettability and bonding strength, thereby optimizing the micro-dispersion and strengthening effect of the nano-ZrB2 particles. Simultaneously, both CeO2 and nano-ZrB2 particles refine the matrix grains, inhibit weld crack initiation and propagation, and improve weld formation. Therefore, Example 1 achieved the highest maximum tensile strength.
[0083] In summary, this invention can achieve the technical effect of improving the average hardness and tensile strength of aluminum-based composite material / duplex steel welded joints.
[0084] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
Claims
1. A laser welding method for aluminum-based composite materials / duplex steel, characterized in that, Includes the following steps: A solvent was added to a mixture of aluminum powder and CeO2 powder to obtain Al-CeO2; the mass fraction of CeO2 powder in the mixture was 30wt% to 60wt%. Al-CeO2 loaded on ZrB 2p / 6061Al composite material surface to be welded, forming an intermediate layer powder, to obtain pretreated aluminum matrix composite material; ZrB 2p In the / 6061Al composite material, the mass fraction of nano-ZrB2 particles is 4wt%~8wt%; on the surface of the pretreated aluminum matrix composite material to be welded, the loading of the intermediate layer powder is 22mg / cm². 2 ~40mg / cm 2 ; A welding method is adopted, with duplex steel sheet on top and pretreated aluminum matrix composite material on the bottom, and Al-CeO2 in the middle. The pretreated aluminum matrix composite material and duplex steel sheet are fixed in a welding fixture. In an inert atmosphere, after the solvent in the intermediate layer powder evaporates, laser welding is performed. The laser beam penetrates the upper duplex steel sheet to form a deep-penetrating micropore and melts the lower pretreated aluminum matrix composite material to form a molten pool. The nano-ZrB2 particles in the weld refine the grains of the molten pool and pin dislocations. At the same time, CeO2 in the intermediate layer powder is adsorbed at the Al-Fe interface to inhibit element interdiffusion and reduce the formation of brittle Al-Fe intermetallic compounds. Meanwhile, the nano-ZrB2 particles and CeO2 produce a synergistic strengthening effect, which enhances the mechanical properties of the weld.
2. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, The diameter of CeO2 powder is 60nm to 100nm, and the diameter of aluminum powder is 70μm to 150μm.
3. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, The laser power for laser welding is 1500W to 2000W, and the welding speed is 15mm / s to 24mm / s.
4. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, The pretreated aluminum matrix composite material and the duplex steel plate have the same length, width and height.
5. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, The overlap length of the duplex steel sheet and the pretreated aluminum matrix composite material in the width direction is >8mm.
6. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, Before laser welding, ZrB was also subjected to... 2p The surfaces of the 6061Al composite material and duplex steel plates to be welded are finely ground, cleaned, and dried.
7. The laser welding method for aluminum-based composite materials / duplex steel according to claim 1, characterized in that, Before loading Al-CeO2, ZrB was also subjected to... 2p The surface of the 6061Al composite material to be welded was grooved.
Citation Information
Patent Citations
Laser welding method for dual-phase steel and aluminum alloy with preset nano rare earth intermediate layer
CN120170269A